2006
DOI: 10.1002/jcb.21112
|View full text |Cite
|
Sign up to set email alerts
|

Oxysterol‐induced osteoblastic differentiation of pluripotent mesenchymal cells is mediated through a PKC‐ and PKA‐dependent pathway

Abstract: Oxysterols form a large family of oxygenated derivatives of cholesterol that are present in circulation, and in human and animal tissues. The discovery of osteoinductive molecules that can induce the lineage-specific differentiation of cells into osteoblastic cells and therefore enhance bone formation is crucial for better management of bone fractures and osteoporosis. We previously reported that specific oxysterols have potent osteoinductive properties and induce the osteoblastic differentiation of pluripoten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 51 publications
4
42
0
1
Order By: Relevance
“…Similar to the pluripotent marrow stromal cells, we found that C3H10T1/2 cells undergo osteoblastic differentiation in response to oxysterols, as assessed by the induction of ALP activity (Fig. 4a) and Runx2 DNA binding activity (18). Treatment with oxysterols also induced Gli-luc activity in C3H10T1/2 cells, and this activity was inhibited by cyclopamine pre-treatment (Fig.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Similar to the pluripotent marrow stromal cells, we found that C3H10T1/2 cells undergo osteoblastic differentiation in response to oxysterols, as assessed by the induction of ALP activity (Fig. 4a) and Runx2 DNA binding activity (18). Treatment with oxysterols also induced Gli-luc activity in C3H10T1/2 cells, and this activity was inhibited by cyclopamine pre-treatment (Fig.…”
Section: Resultsmentioning
confidence: 70%
“…Role of PKC and PKA in Oxysterol-induced Hh Pathway Activation-We previously reported that oxysterol-induced osteoblastic differentiation of cells is mediated via protein kinase C (PKC)-and protein kinase A (PKA)-dependent mechanisms (18). The role of these signaling pathways in regulating the different markers of osteoblastic differentiation appears to be both specific and overlapping (18).…”
Section: Studies Using Ptchmentioning
confidence: 99%
See 1 more Smart Citation
“…These results reveal a prominent role for PKC␣ in osteoblast differentiation induced by MT FGFR2 in murine mesenchymal cells. A positive role of PKC in the regulation of osteoblast differentiation is supported by the recent finding that PKC activation increases osteoblast gene expression (62,63). Whether PKC␣ may up-regulate directly osteoblast gene expression is an interesting question.…”
Section: Discussionmentioning
confidence: 96%
“…Reported activities include regulation of Runx2 expression and activity [99], increasing the expression of BMP receptor IA [128], stimulating fibronectin expression [129,130] enhancing N-Cadherin expression [131], and increasing indexes of the osteoblast phenotype in MC3T3, C2C12, C3H10T1/2, M2-10B4 mouse bone marrow stromal cells [132], primary cultured rat osteoblasts and human calvaria osteoblasts.…”
Section: Introductionmentioning
confidence: 99%